PEMBERIAN PUPUK UREA DAN PUPUK ORGANIK CAIR NASA TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KANGKUNG DARAT (Ipomea Reptans) - Muslihudin Muslihudin; Sugiarto Sugiarto; Abdul Basit (AGRONISMA, 2021)
This study aims to determine the effectiveness of the combination of UREA and liquid organic fertilizers NASA on the growth and quality of land spinach plants (Ipomea Reptans). This research was conducted in Bululawang Subdistrict, Malang Regency and integrated laboratory of Islamic University of Malang with an altitude of ± 460 masl, an average temperature of 22ºC. Rainfall was 675 mm. This research was conducted from April 2020 to May 2020. This study used a factorial randomized block design (RBD) experiment consisting of 2 factors. Factor 1 is the composition of UREA fertilizer consisting of 4 levels, namely M0 (without giving Urea), M1 (100 kg Urea / Ha), M2 (125 kg urea / Ha), M3 (150 kg Urea / Ha). Factor 2 is the concentration of liquid organic fertilizers  NASA which consists of 4 levels, namely, N0 (without giving liquid organic fertilizers NASA), N1 (Giving liquid organic fertilizers Nasa 100 ml / L), N2 (Giving liquid organic fertilizers NASA fertilizer 125 ml / L) and N3 (giving liquid organic fertilizers NASA 150 ml / L) from 2 factors obtained 16 combinations, each treatment had 3 samples and was repeated 3 times so that there were 144 samples.              The results of this study indicate that there is an interaction between UREA fertilizer and liquid organic fertilizers NASA. Based on the results of data analysis in general, it can be said that the combination of Urea fertilizer 150 kg / Ha with 100ml / L liquid organic fertilizers NASA (M3N1) shows better results when compared to controls and other treatments, in increasing height growth, number of leaves, leaf area, weight. total plant freshness and total dry weight of land spinach plants. This is because in the early growth phase to the fast growth phase, kale plants need quite a lot of nutrients. When plants grow and develop, they need a lot of nutrients or nutrients. Provision of UREA fertilizer and NASA POC at the age of 6, 14 and 28 days after planting is very appropriate when at that time the plants need sufficient amounts of nutrients.